Hybrid high-intensity ultrasound and microwave treatment: A review on its effect on quality and bioactivity of foods - Nerea Muñoz-Almagro (Elsevier, 2021)
With the growing of consumer’s demand for products ready to eat that can be elaborated with greener technologies without affecting to their organoleptic characteristics, the application of ultrasound combined with microwaves has been widely studied on food preservation treatments (drying, frying), extraction of high-value added compounds and enzymatic hydrolysis of proteins. This review presents a complete picture of current knowledge on the ultrasound combined with microwaves including the mechanisms, influencing factors, advantages and drawbacks, emphasising in several synergistic effects observed in different processes of strong importance in the food industry. Recent research has shown that this hybrid technology could not only minimise the disadvantages of power US for drying and frying but also improve the product quality and the efficiency of both cooking processes by lowering the energy consumption. Regarding extraction, current studies have corroborated that the combined method presents higher yields in less time, in comparison with those in the respective ultrasound and microwave separately. Additionally, recent results have indicated that the bioactive compounds extracted by this combined technology exhibit promising antitumor activities as well as antioxidant and hepatoprotective effects. Remarkably, this hybrid technology has been shown as a good pre-treatment since the structural changes that are produced in the molecules facilitate the subsequent action of enzymes. However, the combination of these techniques still requires a proper design to develop and optimized conditions are required to make a scale process, and it may lead to a major step concerning a sustainable development and utilization of bioactive compounds from natural products in real life.